1990
DOI: 10.1111/j.1745-9125.1990.tb01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Perspectives in Criminology *

Abstract: For several decades, mainstream criminology has been dominated by sociological and political perspectives. Although findings from these fields must not be discarded or underplayed, considered alone, they do not offer a complete assessment of the contributions to criminal behavior. Data currently being generated from numerous behavioral sciences, such as behavioral genetics, physiological psychology, psychopharmacology, and endocrinology, indicate that biological factors play an equally significant role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
8

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 171 publications
0
40
0
8
Order By: Relevance
“…M. Gottfredson and Hirschi (1990) identify personally persistent and pervasive predispositions as low self-control that often results from ineffective parenting of children; J. Q. Wilson and Herrnstein (1985) refer to high impulsivity and low conscience with more ambiguous sources; while biological criminologists point to a physiological propensity for criminal offending perhaps resulting from low autonomic nervous system conditionability or biochemical imbalances (Fishbein 1990). While differing in their labeling of the predispositions, these formulations agree that a stable and versatile range of outcomes including parental imprisonment and school and child educational failure are products of common causes and resulting processes of self-selection.…”
Section: Intergenerational Student and School Effects Of Imprisoning mentioning
confidence: 99%
“…M. Gottfredson and Hirschi (1990) identify personally persistent and pervasive predispositions as low self-control that often results from ineffective parenting of children; J. Q. Wilson and Herrnstein (1985) refer to high impulsivity and low conscience with more ambiguous sources; while biological criminologists point to a physiological propensity for criminal offending perhaps resulting from low autonomic nervous system conditionability or biochemical imbalances (Fishbein 1990). While differing in their labeling of the predispositions, these formulations agree that a stable and versatile range of outcomes including parental imprisonment and school and child educational failure are products of common causes and resulting processes of self-selection.…”
Section: Intergenerational Student and School Effects Of Imprisoning mentioning
confidence: 99%
“…49 Studies have shown that animals on a tryptophan-poor diet presented high rates of aggressive behavior. 50 In children, zinc and/or iron deficiencies are also related to increased aggressive behavior 51,52 since iron deficiency may reduce dopaminergic transmission.…”
Section: ) Nutritionalmentioning
confidence: 99%
“…Physical aggression has been linked to increased involvement in criminal behaviour (Doidge 2007;Dutton 2002;Fishbein 2001). The early adolescent attraction towards physical acts of aggression manifests itself in the graffiti context as 'slashing' (i.e., the drawing a line through someone else's or another crew's tag).…”
Section: The Rush Achieved From Engaging In An Aggressive Actmentioning
confidence: 99%